2014
DOI: 10.1016/j.exer.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of signal peptide peptidase (SPP) affect HSV-1 infectivity in vitro and in vivo

Abstract: Recently we have shown that the highly conserved herpes simplex virus glycoprotein K (gK) binds to signal peptide peptidase (SPP), also known as minor histocompatibility antigen H13. In this study we have demonstrated for the first time that inhibitors of SPP, such as L685,458, (Z-LL)2 ketone, aspirin, ibuprofen and DAPT, significantly reduced HSV-1 replication in tissue culture. Inhibition of SPP activity via (Z-LL)2 ketone significantly reduced viral transcripts in the nucleus of infected cells. Finally, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 77 publications
3
31
3
Order By: Relevance
“…Our current results suggest that the effects of the ribozyme reduction in UL20 expression could be associated with a reduction in the binding of UL20 to HSV-1 gK. Previously, we have shown that HSV-1 gK binds to SPP and that short hairpin RNA (shRNA) against SPP, SPP dominantnegative mutants, and SPP inhibitors were all able to reduce HSV-1 titers in vitro (28,41). SPP is an endoplasmic reticulum (ER) protein (42,43), whereas GODZ is a Golgi protein (23,44).…”
Section: Discussionmentioning
confidence: 79%
“…Our current results suggest that the effects of the ribozyme reduction in UL20 expression could be associated with a reduction in the binding of UL20 to HSV-1 gK. Previously, we have shown that HSV-1 gK binds to SPP and that short hairpin RNA (shRNA) against SPP, SPP dominantnegative mutants, and SPP inhibitors were all able to reduce HSV-1 titers in vitro (28,41). SPP is an endoplasmic reticulum (ER) protein (42,43), whereas GODZ is a Golgi protein (23,44).…”
Section: Discussionmentioning
confidence: 79%
“…Notably, we have also found that HSV-1 gK binds to HSV-1 UL20 and that this interaction is required for transport of gK to the surface in infected cells (1,2). Further analysis of the intracellular interactions of HSV-1 gK and UL20 have revealed that gK binds to signal peptide peptidase (SPP), an ER protein (35,36), and that UL20 binds to GODZ, a Golgi apparatus protein (6). In those studies, we showed that either blockade of UL20 binding to GODZ or blockade of gK binding to SPP reduces HSV-1 infectivity, as well as gK and UL20 localization, respectively, in vitro.…”
Section: Discussionmentioning
confidence: 86%
“…gK binding to HSV-1 UL20 was previously shown using two-hybrid and pulldown assays, and we have now shown that gK, but no other HSV-1 genes, specifically binds to signal peptide peptidase (SPP) (20). SPP dominant negative mutants and a short hairpin RNA (shRNA) against SPP significantly reduced HSV-1 replication in vitro (20), while SPP inhibitors reduced virus infectivity in vivo (21).…”
mentioning
confidence: 73%
“…Based on our previously published study, SPP may also play a significant role in HSK (20,21). However, SPP is an essential gene, and mice lacking SPP are embryonic lethal (39).…”
mentioning
confidence: 98%